Trabeculectomy and Combined Phacoemulsification-Trabeculectomy: Outcomes and Risk Factors for Failure in Primary Angle Closure Glaucoma. Issue 9 (September 2016) - Song, Brian J.; Ramanathan, Meera; Morales, Esteban; Law, Simon K.; Giaconi, JoAnn A.; Coleman, Anne L.; Caprioli, Joseph
Abstract : Purpose: To evaluate tonometric outcomes of patients with primary angle closure glaucoma (PACG) who have undergone trabeculectomy with mitomycin C (MMC) with and without concurrent phacoemulsification and to identify risk factors for postoperative failure. Patients and Methods: Retrospective cohort study of 44 eyes of 33 phakic patients who underwent trabeculectomy with MMC with or without combined phacoemulsification for PACG. The primary endpoint was qualified tonometric success at 12 months according to predefined criteria. LogMAR visual acuity, number of glaucoma medications, and postoperative complications were also evaluated. Cox proportional hazard regression analysis was performed to identify potential risk factors for trabeculectomy failure. Results: Mean intraocular pressure (IOP) decreased from 21.3±7.9 to 12.2±3.9 mm Hg at 12 months ( P <0.001) in all patients. A significant reduction in mean number of glaucoma medications ( P <0.001) was also seen. There was no change in logMAR visual acuity ( P =0.39) after 12 months. There were no significant intergroup differences in mean IOP ( P =0.42), number of glaucoma medications ( P =0.85), or logMAR visual acuity ( P =0.42) between the trabeculectomy versus combined surgery groups after 12 months. Increased age, greater baseline IOP, limbus-based conjunctival flaps, and MMC duration >1 minute were associated with decreased risk of surgical failure. Concurrent phacoemulsification at the time of trabeculectomy did not alter tonometric success or rate of complications. Conclusions: In phakic patients with PACG, trabeculectomy with MMC significantly reduces IOP and number of glaucoma medications at 12 months without change in visual acuity. However, success rates are modest when based on more demanding tonometric criteria.